Runoff Estimation from a Small Watershed Using Giuh Approach in a GIS Environment - M. K. Nema,; J. K. Singh,; A. K. Lohani, (Journal of Soil and Water Conservation, 2022)
Two conceptual models namely GIUH based Clark and GIUH based Nash for Kothuwatari (29.67 km-2) watershed, a sub-watershed of upper Damodar Valley, Hazaribagh, Jharkhand, India were developed for estimating direct surface runoff hydrographs on storm basis. The model parameters of both the models were determined by Newton-Rapson non-linear optimization technique, using the Geomorphological characteristics of the watershed. The various geomorphologic characteristics of the study watershed have been determined from the toposheets 72H/7 and 72H/8 by using the GIS software ILWIS 3.0. The performance of the models has been evaluated by employing performance indices viz., coefficient of efficiency, absolute average error, root mean square error, average error in volume and absolute percentage deviation in peak flow rates. The results of the study showed that both the developed models provide a reasonably good estimate of direct surface runoff based on these performance indices. However, it was difficult to conclude that which model performs better for the study area as based on percentage absolute deviation in peak and average error in volume, the GIUH based Clark model was found better while based on rest of the indices the GIUH based Nash model was found better.